Semiautomated glycoproteomics data analysis workflow for maximized glycopeptide identification and reliable quantification - Lippold, Steffen; de Ru, Arnoud H.; Nouta, Jan; van Veelen, Peter A.; Palmblad, Magnus; Wuhrer, Manfred; de Haan, Noortje (Beilstein Journal of Organic Chemistry, 2020)
Glycoproteomic data are often very complex, reflecting the high structural diversity of peptide and glycan portions. The use of glycopeptide-centered glycoproteomics by mass spectrometry is rapidly evolving in many research areas, leading to a demand in reliable data analysis tools. In recent years, several bioinformatic tools were developed to facilitate and improve both the identification and quantification of glycopeptides. Here, a selection of these tools was combined and evaluated with the aim of establishing a robust glycopeptide detection and quantification workflow targeting enriched glycoproteins. For this purpose, a tryptic digest from affinity-purified immunoglobulins G and A was analyzed on a nano-reversed-phase liquid chromatography–tandem mass spectrometry platform with a high-resolution mass analyzer and higher-energy collisional dissociation fragmentation. Initial glycopeptide identification based on MS/MS data was aided by the Byonic software. Additional MS1-based glycopeptide identification relying on accurate mass and retention time differences using GlycopeptideGraphMS considerably expanded the set of confidently annotated glycopeptides. For glycopeptide quantification, the performance of LaCyTools was compared to Skyline, and GlycopeptideGraphMS. All quantification packages resulted in comparable glycosylation profiles but featured differences in terms of robustness and data quality control. Partial cysteine oxidation was identified as an unexpectedly abundant peptide modification and impaired the automated processing of several IgA glycopeptides. Finally, this study presents a semiautomated workflow for reliable glycoproteomic data analysis by the combination of software packages for MS/MS- and MS1-based glycopeptide identification as well as the integration of analyte quality control and quantification.
Keywords: bioinformatics; cysteine oxidation; glycoproteomics; immunoglobulins; mass spectrometry

(untitled) - Fu, C.; Zhao, H.; Wang, Y.; Cai, H.; Xiao, Y.; Zeng, Y.; Chen, H. (HLA, 2016)

(untitled) - Szabo, Z.; Thayer, J. R.; Reusch, D.; Agroskin, Y.; Viner, R.; Rohrer, J.; Patil, S. P.; Krawitzky, M.; Huhmer, A.; Avdalovic, N.; Khan, S. H.; Liu, Y.; et al. (J. Proteome Res., 2018)

(untitled) - de Haan, N.; Falck, D.; Wuhrer, M. (Glycobiology, 2020)

(untitled) - Yang, Y.; Franc, V.; Heck, A. J. R. (Trends Biotechnol., 2017)

(untitled) - Pan, S.; Chen, R.; Aebersold, R.; Brentnall, T. A. (Mol. Cell. Proteomics, 2011)

(untitled) - Stavenhagen, K.; Hinneburg, H.; Thaysen-Andersen, M.; Hartmann, L.; Silva, D. V.; Fuchser, J.; Kaspar, S.; Rapp, E.; Seeberger, P. H.; Kolarich, D. (J. Mass Spectrom., 2013)

(untitled) - Thaysen-Andersen, M.; Packer, N. H. (Biochim. Biophys. Acta, Proteins Proteomics, 2014)

(untitled) - Ozohanics, O.; Turiák, L.; Puerta, A.; Vékey, K.; Drahos, L. (J. Chromatogr. A, 2012)

(untitled) - Ruhaak, L. R.; Xu, G.; Li, Q.; Goonatilleke, E.; Lebrilla, C. B. (Chem. Rev., 2018)

(untitled) - Klein, J.; Zaia, J. (J. Proteome Res.)

(untitled) - Lee, L. Y.; Moh, E. S. X.; Parker, B. L.; Bern, M.; Packer, N. H.; Thaysen-Andersen, M. (J. Proteome Res., 2016)

(untitled) - Abrahams, J. L.; Taherzadeh, G.; Jarvas, G.; Guttman, A.; Zhou, Y.; Campbell, M. P. (Curr. Opin. Struct. Biol., 2020)

(untitled) - Hu, H.; Khatri, K.; Zaia, J. (Mass Spectrom. Rev., 2017)

(untitled) - Bern, M.; Kil, Y. J.; Becker, C. (Curr. Protoc. Bioinf., 2012)

(untitled) - Choo, M. S.; Wan, C.; Rudd, P. M.; Nguyen-Khuong, T. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Jansen, B. C.; Falck, D.; de Haan, N.; Hipgrave Ederveen, A. L.; Razdorov, G.; Lauc, G.; Wuhrer, M. (J. Proteome Res., 2016)

(untitled) - Momčilović, A.; de Haan, N.; Hipgrave Ederveen, A. L.; Bondt, A.; Koeleman, C. A. M.; Falck, D.; de Neef, L. A.; Mesker, W. E.; Tollenaar, R.; de Ru, A.; van Veelen, P.; Wuhrer, M.; et al. (Anal. Chem. (Washington, DC, U. S.), 2020)

(untitled) - Plomp, R.; de Haan, N.; Bondt, A.; Murli, J.; Dotz, V.; Wuhrer, M. (Front. Immunol., 2018)

(untitled) - Šimurina, M.; de Haan, N.; Vučković, F.; Kennedy, N. A.; Štambuk, J.; Falck, D.; Trbojević-Akmačić, I.; Clerc, F.; Razdorov, G.; Khon, A.; Latiano, A.; D'Incà, R.; et al. (Gastroenterology, 2018)

(untitled) - Alocci, D.; Mariethoz, J.; Gastaldello, A.; Gasteiger, E.; Karlsson, N. G.; Kolarich, D.; Packer, N. H.; Lisacek, F. (J. Proteome Res., 2019)

High-Throughput Glycomics and Glycoproteomics: Methods and Protocols - Falck, D.; Jansen, B. C.; de Haan, N.; Wuhrer, M. (High-Throughput Analysis of IgG Fc Glycopeptides by LC-MS, 2017)

(untitled) - Deshpande, N.; Jensen, P. H.; Packer, N. H.; Kolarich, D. (J. Proteome Res., 2010)

(untitled) - Chandler, K. B.; Mehta, N.; Leon, D. R.; Suscovich, T. J.; Alter, G.; Costello, C. E. (Mol. Cell. Proteomics, 2019)

(untitled) - Zheng, S.; Doucette, A. A. (Proteomics, 2016)

Mass Spectrometry of Glycoproteins: Methods and Protocols - Nilsson, J.; Larson, G. (Humana Press, 2013)

(untitled) - Joenväärä, S.; Ritamo, I.; Peltoniemi, H.; Renkonen, R. (Glycobiology, 2008)

(untitled) - Steen, H.; Mann, M. (J. Am. Soc. Mass Spectrom., 2001)

(untitled) - Gupta, V.; Carroll, K. S. (Biochim. Biophys. Acta, Gen. Subj., 2014)

(untitled) - Darula, Z.; Medzihradszky, K. F. (Anal. Chem. (Washington, DC, U. S.), 2015)

(untitled) - Delafield, D. G.; Li, L. (Mol. Cell. Proteomics)

(untitled) - Kil, Y. J.; Becker, C.; Sandoval, W.; Goldberg, D.; Bern, M. (Anal. Chem. (Washington, DC, U. S.), 2011)

(untitled) - Rebecchi, K. R.; Wenke, J. L.; Go, E. P.; Desaire, H. (J. Am. Soc. Mass Spectrom., 2009)

(untitled) - Sturm, M.; Bertsch, A.; Gröpl, C.; Hildebrandt, A.; Hussong, R.; Lange, E.; Pfeifer, N.; Schulz-Trieglaff, O.; Zerck, A.; Reinert, K.; Kohlbacher, O. (BMC Bioinf., 2008)

(untitled) - Röst, H. L.; Sachsenberg, T.; Aiche, S.; Bielow, C.; Weisser, H.; Aicheler, F.; Andreotti, S.; Ehrlich, H.-C.; Gutenbrunner, P.; Kenar, E.; Liang, X.; Nahnsen, S.; et al. (Nat. Methods, 2016)